Penerapan Model Pembelajaran Kausalitik Untuk Meningkatkan Kemampuan Bernalar Dalam Pembelajaran Fisika Masa Learning from Home Pandemi Covid-19 - Nurjamilah Nurjamilah; Joni Rokhmat; Hairunnisyah Sahidu; Ahmad Harjono (Department of Physics Education, Universitas Mataram, 2020)
The Covid-19 pandemic requires teachers to make innovations in learning, such as utilizing appropriate applications and choosing the right learning model to encourage students' reasoning abilities. This study aims to identify the effect of the causal learning model on students' reasoning abilities in learning physics during the learning from home period due to the Covid-19 pandemic. This type of research is a quasi-experimental study with a 2x2 factorial design. The population is all students of class X MIA Madrasah Aliyah Negeri 2 (MAN 2) Mataram. Sampling using purposive sampling technique so that selected students of class X-MIA 3 (31 students) as the experimental class and class X-MIA 4 (30 students) as the control class. The instrument used to measure reasoning ability was a description test of 4 items. The results showed that the data were normally distributed and homogeneous with the chi-squarecount (10.390) <chi-squaretable (11.070), (experimental class); chi-squarecount (10,873) <chi-squaretable (11,070), (control class); and Fcount (1,502) <Ftable (1,799). The hypothesis was tested using the t-test with a significance level (sig.) Of 5%. Hypothesis test results show the sig value. smaller than 0.05 (Ã°ÂâºÂ¼ <0.05) (Ã°ÂÂÂ»0 rejected) and the experimental class gain (56.02%, moderate) is higher than the gain for the control class (38.28%, low). The conclusion is that the causal learning model has an effect on improving students' reasoning ability in learning physics during the learning from home period due to the Covid-19 pandemic. Recommendations that can be given in an effort to improve students 'reasoning abilities are to present physical phenomena in the form of pictures that can stimulate students' thinking activities.